1999
DOI: 10.1093/oxfordjournals.aje.a009958
|View full text |Cite
|
Sign up to set email alerts
|

Risk of End-stage Renal Disease Associated with Alcohol Consumption

Abstract: Alcohol consumption has been linked to kidney disorders in selected patient groups, but whether it contributes to the burden of end-stage renal disease (ESRD) in the general population is unknown. The authors conducted a population-based case-control study to assess the relation between alcohol consumption and risk of ESRD. The study took place in Maryland, Virginia, West Virginia, and Washington, DC, in 1991. Participants were 716 patients who had started treatment for ESRD and 361 control subjects of simila… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
72
0
1

Year Published

2003
2003
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 115 publications
(77 citation statements)
references
References 45 publications
4
72
0
1
Order By: Relevance
“…However, as insulin sensitivity was associated with GFR in individuals with otherwise normal glucose metabolism after adjustment for both fasting and postload glucose levels, higher glucose levels are not a likely explanation for the results in the present study. Also, insulin sensitivity is associated with several glucometabolic, cardiovascular risk, and lifestyle factors that have been shown to be associated with a reduced GFR and the development of chronic kidney disease (2,12,(21)(22)(23). The fact that insulin sensitivity remained significantly associated with GFR in all multivariable models suggests that confounding by these factors does not explain our findings.…”
Section: Modelmentioning
confidence: 71%
“…However, as insulin sensitivity was associated with GFR in individuals with otherwise normal glucose metabolism after adjustment for both fasting and postload glucose levels, higher glucose levels are not a likely explanation for the results in the present study. Also, insulin sensitivity is associated with several glucometabolic, cardiovascular risk, and lifestyle factors that have been shown to be associated with a reduced GFR and the development of chronic kidney disease (2,12,(21)(22)(23). The fact that insulin sensitivity remained significantly associated with GFR in all multivariable models suggests that confounding by these factors does not explain our findings.…”
Section: Modelmentioning
confidence: 71%
“…On the one hand, alcohol consumption has been associated with the risk of CKD. 28,33 A population-based cohort study in the United States reported that drinking ⩾ 4 servings daily was independently associated with an increased CKD risk 28 (each serving of beer, wine and liquor was considered to contain 12.96, 11.48 and 14.00 g of ethanol, respectively 34 ). A case-control study in the United States reported that the consumption of more than two alcoholic drinks per day was associated with an increased risk of ESRD and that a lower intake of alcohol did not appear to be harmful.…”
Section: Discussionmentioning
confidence: 99%
“…A case-control study in the United States reported that the consumption of more than two alcoholic drinks per day was associated with an increased risk of ESRD and that a lower intake of alcohol did not appear to be harmful. 33 On the other hand, alcohol consumption has been inversely associated with the risk of CKD. [25][26][27][35][36][37] A prospective cohort study of 11 023 initially healthy male physicians in the United States reported a significantly lower risk of renal dysfunction (defined as serum creatinine ⩾ 1.5 mg/dl and eGFR ⩽ 55 ml/min) in those who consumed at least 7 drinks weekly.…”
Section: Discussionmentioning
confidence: 99%
“…We could not find any potential harmful effects regarding the frequency of drinking alcohol on CKD. A case-control study of 716 patients with incident ESRD and 361 age-matched population controls conducted by Perneger et al [15] showed the presence of a significantly increased risk of ESRD among individuals who consumed more than 2 drinks per day as compared with those who abstained from alcohol (OR: 4.0; 95% CI, 1.2-13.0). In addition, Shankar et al [12] examined the association between CKD and heavy alcohol consumption in a 5-year longitudinal analysis of 3,392 Americans without CKD.…”
Section: Discussionmentioning
confidence: 99%
“…However, epidemiological studies of the relationship between alcohol consumption and CKD are scarce. A few studies have indicated that moderate alcohol consumption was not associated with increased risk of renal dysfunction [13] and was associated with only a low risk of cardiovascular mortality in CKD patients [14], whereas other studies showed that heavy drinking was associated with a high risk of CKD [12] and end-stage renal disease (ESRD) [15]. In addition, a few previous studies [9,16] showed that alcohol consumption was not associated with CKD.…”
Section: Introductionmentioning
confidence: 99%